2015
DOI: 10.3390/ijerph120707910
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Consumption of Caffeinated Energy Drinks among Polish Adolescents

Abstract: Background: Energy drinks (EDs) are extremely popular among adults and adolescents. Regular intake of EDs may lead to an overdose of caffeine, loss of bone mass, overweight, hypertension and, in older age, osteoporosis and cardiovascular diseases. Some people mix EDs with alcohol, which adversely affects their health. The objective of this study was to analyze the consumption of EDs by adolescents. Methods: The study consisted of a questionnaire surveying amounts of drinks, preferences and product awareness am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
87
5
6

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 84 publications
(116 citation statements)
references
References 24 publications
(45 reference statements)
13
87
5
6
Order By: Relevance
“…In our study, 69% of students consumed EDs, 17% of whom had EDs often, every day or 1 to 3 times a week. This study demonstrated that EDs consumption among adolescent athletes was slightly higher than among students from other schools, which we had analyzed previously [30]. Some students drinking EDs reported health problems, such as: abdominal pain, arrhythmia, nausea.…”
Section: Discussionsupporting
confidence: 52%
“…In our study, 69% of students consumed EDs, 17% of whom had EDs often, every day or 1 to 3 times a week. This study demonstrated that EDs consumption among adolescent athletes was slightly higher than among students from other schools, which we had analyzed previously [30]. Some students drinking EDs reported health problems, such as: abdominal pain, arrhythmia, nausea.…”
Section: Discussionsupporting
confidence: 52%
“…The principal source of caffeine are beverages namely cola and mainly coffee, which was confirmed in our study [12].…”
Section: Frequency and Pattern Of Caffeinated Energy Drink Consumptionsupporting
confidence: 71%
“…However, several research articles showed multiple negative effects of the consumption of energy and soft drinks. The consumers claim that these drinks, especially energy drinks, provide them with the energy required for stressful situations, or for staying awake for a longer time (Nowak & Jasionowski, 2015).…”
Section: Discussionmentioning
confidence: 99%